Oakhill, Clay County - Schnee, Angela (Kansas State University, The Chapman Center for Rural Studies, 2012)
Oakhill, Kansas, located in Oakland Township in southwest Clay County, may appear to be just another Kansas town. However, the history of this little place paints a unique picture that is unlike other vanishing communities in Kansas. Many Kansas towns can be categorized into one of the several settlement patterns that have characterized the history of Kansas. Oakhill fits almost all of them. It is easily qualified as a frontier town, a paper town, and a railroad town; this diverse history of settlement in Oakhill is quite unusual and creates a rare and interesting town history.
Angela Schnee, “Oakhill, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/68.
Keywords: Chapman's Creek; Clay County; Dieter Farm; Oak Hill; Oakhill; Oakland Township